Community faecal carriage of extended-spectrum beta-lactamase-producing Enterobacteriaceae in french children - Birgy, André (BioMed Central, 2012)
BACKGROUND: The increasing incidence of community acquired infection due to Extended-Spectrum Beta-Lactamase (ESBL) -Producing Enterobacteriaceae represent a great concern because there are few therapeutic alternatives. The fecal flora of children in the community can represent a reservoir for ESBLs genes which are located on highly transmissible plasmids and the spread of these genes among bacterial pathogens is concerning. Because intestinal carriage is a key factor in the epidemiology of ESBL-producing Enterobacteriaceae, the study of the prevalence of these resistant bacteria and risk factors in young children is of particular interest. METHODS: We assessed the prevalence and risk factors of community-acquired faecal carriage of extended-spectrum-β-lactamase (ESBL)-producing Enterobacteriaceae in children aged from 6 to 24 months, by means of rectal swabbing in community pediatric practices. Child’s lifestyle and risk factors for carriage of resistant bacteria were noted. RESULTS: Among the 411 children enrolled, 4.6% carried ESBL-producing Enterobacteriaceae. CTX-M-1, CTX-M-15 and CTX-M-14 were the predominant ESBLs. The 18 E. coli isolates were genetically heterogeneous. Recent third-generation oral-cephalosporin exposure was associated with a higher risk of ESBL carriage (AOR=3.52, 95% CI[1.06-11.66], p=0.04). CONCLUSIONS: The carriage rate of ESBL-producing Enterobacteriacae in young children in the French community setting is noteworthy, underlining the importance of this population as a reservoir. Exposure to third-generation oral cephalosporins was associated with a significant risk of ESBL carriage in our study. Because of the significant public health implications including the treatment of community-acquired urinary tract infections, the spread of organisms producing ESBLs in the community merits close monitoring with enhanced efforts for surveillance.